Pelaksanaan Pemungutan Suara Ulang Dalam Pemilukada Di Kota Cirebon Tahun 2018 - Ardhi Rachmat Ramadhan; Sodikin Sodikin (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
AbstractThis study aims to determine the legal considerations of the Constitutional Court judges in deciding the implementation of the re-voting in the election of the Mayor and Deputy Mayor of the City of Cirebon in 2018 by reviewing the theory of democracy, popular sovereignty, and the rule of law. In the Cirebon City Election in 2018, there was a fraud in the Election with the opening of the ballot box against the law, thus affecting the vote acquisition that harms the Candidate Pair, namely Candidate Pair Number One with a smaller vote than the Candidate Pair Number two. This research uses normative-juridical type and library research by conducting an assessment of the laws and regulations, books, journals, and sources from the related internet. The results showed that the Constitutional Court's Decision was in accordance with the laws and regulations related to the General Election, because the Petitioner had the legal authority to submit to the Constitutional Court and it was proven that there had been an election ballot box opening against the law, so a repeat vote had to be conducted, so that the results of the vote could be recognized by the Petitioner in accordance with the principles of a democratic Regional Head General Election.Keywords: Voting, Election, Constitutional Court